Lesson Outline - Kozka, Iryna (My University, 2016)
The success of lesson planning is achieved if the teacher takes some crucial factors in consideration. Analysis of the content of the teaching material allows the teacher to formulate the main practical, educational, educative and developmental aims. Успіх у плануванні занять досягається, якщо викладач приймає до уваги деякі найважливіші фактори. Аналіз змісту навчального матеріалу дозволяє викладачеві зформувати основні практичні, освітні, виховні та розвиваючі цілі.
Keywords: out-of-class activities; success of lesson planning; formation of habits and skills; problem-solving task; feedback; позакласна робота; успіх у плануванні занять; формування навичок та вмінь; проблемне завдання; зворотній зв’язок